Effects of Temperature and Load on Wear for Different Matrix And Fibre-Reinforced Composite Materials - Pihtili, Hasim; Kocabas, Ibrahim; Cetinkaya, Sukru (Trans Tech Publications Ltd, 2010)
In this study, wear behaviours of fiber-reinforced and matrix composite materials are experimentally investigated under different speeds, loads and temperature. Composite materials were made of Kevlar-epoxy resin, glass fibre-epoxy resin and glass fibre -polyester resin materials. Tests were conducted for speeds of 0.390 and 0.557 m/s at two different loads of 5N and 10N respectively. Wear in the experiments was determined as lost in mass.In addition, the wear behaviour of samples was investigated through the SEM observation.
3rd International Conference on Multi-Functional Materials and Structures -- SEP 14-18, 2010 -- Chonbuk Natl Univ, Jeollabuk do, Jeonju, SOUTH KOREA
Keywords: Wear; Glass fibers; Woven fabric polyester resin; Epoxy resin; Composite materials